Body size and shape misperception and visual adaptation: An overview of an emerging research paradigm. (December 2017) - Challinor, Kirsten L.; Mond, Jonathan; Stephen, Ian D.; Mitchison, Deborah; Stevenson, Richard J.; Hay, Phillipa; Brooks, Kevin R.
Although body size and shape misperception (BSSM) is a common feature of anorexia nervosa, bulimia nervosa and muscle dysmorphia, little is known about its underlying neural mechanisms. Recently, a new approach has emerged, based on the long-established non-invasive technique of perceptual adaptation, which allows for inferences about the structure of the neural apparatus responsible for alterations in visual appearance. Here, we describe several recent experimental examples of BSSM, wherein exposure to "extreme" body stimuli causes visual aftereffects of biased perception. The implications of these studies for our understanding of the neural and cognitive representation of human bodies, along with their implications for clinical practice are discussed.